Factors related to the compliance to consuming iron-folic acid in young women in East Kalimantan, Indonesia - Fikri Thifal; Reny Noviasty; Uzah Maria Ulfa; Lioni Farahita; Ari Utari; Eva R Kurniawati; Ratih Wirapuspita Wisnuwardani (AcTion: Aceh Nutrition Journal, 2023)
Weekly Iron Folic Acid supplementation/WIFAS program for adolescent girls is an effective strategy for preventing anemia. However, in Indonesia, only 1,4% adhere to taking WIFAS. This study aimed to discover the factors related to adolescent girls’ adherence to consuming WIFAS in East Kalimantan. The design of this study was cross-sectional, using a purposive sampling technique to find a sample of 825 adolescent girls. The research location was the East Kalimantan Provincial Health Office from November 15 to December 15, 2021. The analytical method uses the Chi-Square test and binary logistic regression test. The results showed that the level of adherence to the consumption of iron folic acid for adolescents girl was 17,6%. The factors related to the adherence of adolescent girls in consuming WIFAS in East Kalimantan were the area of residence (p=0,023), hemoglobin check (р=0,0001), access to information on iron-folic acid (p=0,014), received/purchased iron-folic acid (p=0,000), knowledge (p=0,010) and the use of the Cegah Anemia Remaja Indonesia (CERIA) application (р=0,0001). Based on reg log analysis, factors such as having received/purchased iron WIFAS, Hb checks, knowledge, and use of the CERIA application were associated with adolescent girls’ adherence to WIFAS. In conclusion, adolescent girls with regular WIFAS consumption were easier to get WIFA, check Hb, have good knowledge and use the CERIA application. These findings suggest the need to carry out hemoglobin checks on adolescent girls, increase the availability of WIFAS and socialize the use of the CERIA app.